2021
DOI: 10.3390/app11125455
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond Optical Nonlinearity of Nanodiamond Suspensions

Abstract: High pressure-high temperature (HP-HT) nanodiamonds and detonation nanodiamonds have unique optical properties and are promising materials for various applications in photonics. In this work, for the first time, comparative studies of the nonlinear optical properties of aqueous suspensions of HP-HT and detonation nanodiamonds under femtosecond laser excitation are performed. Using the z-scan technique, it was found that for the same laser pulse parameters HP-HT nanodiamonds exhibited optical limiting due to tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 75 publications
0
0
0
Order By: Relevance
“…In the paper [4], comparative studies of the nonlinear optical properties of aqueous suspensions of high pressure-high temperature (HP-HT) nanodiamonds and detonation nanodiamonds under femtosecond laser excitation are performed. It was shown that at the same parameters of femtosecond laser pumping and experimental conditions, saturable absorption occurred in an aqueous suspension of detonation nanodiamonds accompanied by short-term nonlinear bleaching, while in an aqueous suspension of HP-HT nanodiamonds, two-photon absorption appeared, leading to optical limiting.…”
Section: Summary Of the Articles Of The Issuementioning
confidence: 99%
“…In the paper [4], comparative studies of the nonlinear optical properties of aqueous suspensions of high pressure-high temperature (HP-HT) nanodiamonds and detonation nanodiamonds under femtosecond laser excitation are performed. It was shown that at the same parameters of femtosecond laser pumping and experimental conditions, saturable absorption occurred in an aqueous suspension of detonation nanodiamonds accompanied by short-term nonlinear bleaching, while in an aqueous suspension of HP-HT nanodiamonds, two-photon absorption appeared, leading to optical limiting.…”
Section: Summary Of the Articles Of The Issuementioning
confidence: 99%